Responses of broilers challenged by Eimeria maxima fed with different levels of dietary balanced protein - Freitas, Luís Filipe Villas Boas de [UNESP]; Dorigam, Juliano Cesar de Paula; Reis, Matheus de Paula [UNESP]; Nogueira, Bernardo Rocha Franco [UNESP]; Lizana, Rony Riveiros [UNESP]; Sakomura, Nilva Kazue [UNESP] (Elsevier, 2023)
This study aimed to evaluate the effects of different dietary balanced protein (BP) levels on the gut health, amino acid apparent ileal digestibility (AID), footpad dermatitis lesions, and litter quality in broiler chicks infected with Eimeria maxima. A total of 2400 male 14-day-old Cobb500 broilers were randomly allotted into 10 treatments with six replications containing 40 birds each in a factorial design of 5 × 2. The treatments consisted of five levels of BP (6.66%, 13.32%, 19.98%, 26.64%, and 33.3%), and broilers unchallenged (NCH) or challenged (CH). Broilers in the CH group received 1 mL of Eimeria maxima inoculum (7 × 103 sporulated oocysts/mL). Oocyst count in excreta, visual intestinal modifications score, morphology, and morphometrics of the ileum were used to determine gut health status. Additionally, amino acids and CP AID, litter quality, and footpad dermatitis were evaluated. An ANOVA and Kruskal-Wallis tests followed by post-hoc tests were performed. The oocyst count in the CH group increased with an increase in dieatary BP (P = 0.08). The incidence of intestinal modifications was higher in the CH group (P < 0.05) and increased with increasing dietary BP (P < 0.05). Morphometrics were impaired by the challenge (P < 0.05), and by the two highest BP levels (P < 0.05). Amino acids AID (methionine, methionine + cystine, arginine, and serine) were reduced by E. maxima challenge. An increase in dietary BP resulted in poor litter quality and high prevalence of of footpad dermatitis (P < 0.05). The E. maxima challenge and increased BP decreased gut health, litter quality, and cause a high incidence of footpad dermatitis.
Keywords: Apparent ileal digestibility; Footpad dermatitis; Gut health; Immune parameters; Litter quality